2014
DOI: 10.1007/978-3-319-08072-7_88
|View full text |Cite
|
Sign up to set email alerts
|

EEG-Based Classification of Imagined Arm Trajectories

Abstract: Abstract. A brain-computer interface (BCI) in combination with a neuroprosthesis can be used to restore movement functionalities in paralyzed persons. The BCI detects the movement imagination (MI) and the neuroprosthesis transforms it into a real movement. Today's BCIs can detect the process of MI, but not the actual imagined trajectories of, e.g., the arm. Users' control of a BCI would become more intuitive and natural when the detailed MI, i.e., trajectories, are detected. This is called movement decoding. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In addition to Bradberry et al's work in noninvasive EEG technology, Ofner et al [64] studied the continuous and natural imaginary movements of the right hand in a 2D plane. They estimated the imagined continuous velocities from EEG signals.…”
Section: Imagined Body Kinematics Paradigmsmentioning
confidence: 99%
“…In addition to Bradberry et al's work in noninvasive EEG technology, Ofner et al [64] studied the continuous and natural imaginary movements of the right hand in a 2D plane. They estimated the imagined continuous velocities from EEG signals.…”
Section: Imagined Body Kinematics Paradigmsmentioning
confidence: 99%
“…However, only 1 target was presented on a screen in each trial, and [39] showed that a random cursor also hits this target after some time, and they reached similar decoding results. Thus, we designed a new experiment where subjects imagined arm movements and decoded them (preliminary results have been shown in [40] [41]). However, there is one substantial issue.…”
Section: Introductionmentioning
confidence: 99%